PEMBERDAYAAN UMKM DESA SASAHAN MELALUI PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN AKSES PASAR - Susanto, Denies; Ridwan, Ade (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service program was conducted in Sasahan Village, Waringinkurung District, Serang Regency, Banten, with the aim of empowering Micro, Small, and Medium Enterprises (MSMEs) through digital marketing training to improve market access and business competitiveness. MSMEs in this village face major challenges, including limited digital literacy, lack of skills in managing technology-based marketing, and a continued reliance on conventional methods to expand consumer reach. In fact, digital marketing has been proven as an effective strategy that enables entrepreneurs to utilize social media, online marketplaces, and promotional content to expand their business networks more efficiently. The program implementation consists of several stages, namely problem identification, solution formulation, hands-on training, and continuous monitoring and evaluation. Partner participation is reflected through active involvement in all activities, including providing business data, attending training sessions, independently practicing digital content creation, and establishing a digital MSME community in Sasahan Village. Program evaluation is carried out formatively to adjust training methods according to participants’ needs and summatively to assess improvements in digital literacy, promotional skills, and the overall impact on market access. Program sustainability is supported through online mentoring, collaboration with village authorities, and partnerships with external stakeholders such as online marketplaces and financial institutions. The outcomes of this community service program include improved digital literacy, MSME independence in implementing digital marketing strategies, the establishment of new marketing networks, and an increase in the income and welfare of the Sasahan Village community.